Donald Winnicott’s vision of health. Creative processes as defence mechanisms against anxiety and trauma - Carstea, Daniela (Journal of psychology & clinical psychiatry, 2023)
It could be said that Winnicott’s entire opus revolves around a central issue: the relation between the self and the outside world, between illusion and reality. For Winnicott, the key process is the establishment of a sense of the self experienced as real. The perfect accommodation to the subject’s wish creates what Winnicott terms the “moment of illusion.” In the earliest months of life, Winnicott’s so-called “good enough mother” is invisible, and it is precisely her invisibility which allows the infant the crucial megalomaniacal, solipsistic experience which Winnicott characterizes as the state of “subjective omnipotence.” In his view, a relatively prolonged experience of subjective omnipotence is the foundation upon which a healthy self develops.